Exploring the role of autonomy support and thwarting in the well-being of Iranian early career language teachers - Roshanak Salmani Ghasemzadegan; Ismail Xodabande; Niloufar Koleini; Behruz Lotfi Gaskaree (Discover Psychology)
Abstract Despite growing emphasis on language teachers’ wellbeing over the past years, the wellbeing of early career language has remained largely unexplored. To address this gap, the current qualitative study investigated the perceptions of autonomy support and thwarting among Iranian early career language teachers from the Self-Determination Theory (SDT) perspective. Fifteen early career language teachers (5 males and ten females), were purposefully selected from three private language teaching institutes in Tehran. Data were collected over a six-month period through semi-structured interviews and weekly reflective journals. Thematic analysis was employed to identify recurring patterns and themes in the data. Findings revealed that autonomy-supportive environments fostered teachers’ wellbeing through enhancing intrinsic motivation, professional growth, and job satisfaction, and encouraged teachers to be more effective instructors by enabling them to align their teaching practices with personal values, engage in innovative teaching methods, and pursue skill enhancement opportunities. Participants in supportive contexts reported a harmonious sense of self and described proactive coping strategies, such as seeking collegial support and engaging in reflective practices, to deal with various challenges. Conversely, autonomy-thwarting environments, characterized by micromanagement, limited decision-making authority, and cultural constraints, undermined teachers’ wellbeing as they were associated with feelings of disempowerment, reduced motivation, and professional stagnation. Teachers in these contexts adopted alternative coping strategies, including seeking emotional support from personal networks and engaging in external professional development to counteract the negative effects of thwarting. These findings contribute to the growing body of research on language teacher wellbeing, and underscore the importance of creating autonomy-supportive environments within language teaching institutes, promoting teacher agency, and fostering a sense of ownership among early career teachers.